2003
DOI: 10.1073/pnas.0935295100
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of L-type Ca v 1.3 Ca 2+ channels in cardiac pacemaker activity

Abstract: The spontaneous activity of pacemaker cells in the sino-atrial node (SAN) controls the heart rhythm and rate under physiological conditions. Pacemaker activity in SAN cells is due to the presence of the diastolic depolarization, a slow depolarization phase that drives the membrane voltage from the end of an action potential to the threshold of a new action potential. SAN cells express a wide array of ionic channels, but we have limited knowledge about their functional role in pacemaker activity and we still do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
489
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 434 publications
(518 citation statements)
references
References 21 publications
27
489
1
1
Order By: Relevance
“…In addition, Ca v 1.3 −/− mice reproduce severe AV dysfunction typical of human congenital heart block (16). Previous studies demonstrated that Ca v 1.3-mediated I Ca,L plays a major role in the determination of heart rate and impulse conduction in mice and humans (10,11,14,16,17,19). However, despite the importance of Ca v 1.3-mediated I Ca,L in determining the rate of the diastolic depolarization in isolated SAN and AV node myocytes (14,16), it was unclear how Ca v 1.3 loss of function translates into SSS in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Ca v 1.3 −/− mice reproduce severe AV dysfunction typical of human congenital heart block (16). Previous studies demonstrated that Ca v 1.3-mediated I Ca,L plays a major role in the determination of heart rate and impulse conduction in mice and humans (10,11,14,16,17,19). However, despite the importance of Ca v 1.3-mediated I Ca,L in determining the rate of the diastolic depolarization in isolated SAN and AV node myocytes (14,16), it was unclear how Ca v 1.3 loss of function translates into SSS in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…myocytes, thereby constituting important determinants of heart rate and AV conduction velocity (14,16). The heart rate of mice lacking Ca v 1.3 channels (Ca v 1.3 −/− mice) fairly recapitulates the hallmarks of SSS and associated symptoms, including bradycardia and tachycardia-bradycardia syndrome (17,18).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The inactivated Ca V 1.3 channels in mice induced strong reduction of calcium current in pacemaker cells and profoundly affected its pacemaking effect, which showed predominant sinoatrial nodal dysfunction [124]. With the inactivated Ca V 1.3 calcium currents, both sinoatrial arrhythmia and bradycardia have been observed [23,125].…”
Section: Other Cardiac Arrhythmiasmentioning
confidence: 99%
“…In the initial phase this is mediated by sodium influx via I f , largely constituted by the HCN4 subunit, and as depolarization occurs progressively by T-type calcium channels and finally L-type calcium channels, specifically Ca v 1.3, just prior to threshold and initiation of phase 0. Ca v 1.3 knockout mice have highly unstable pacemaker function with bradycardia and episodes of sinus pauses [12]. The major T-type subunit in the adult animal is Ca v 3.1 and knockout mice are bradycardic [13].…”
Section: An Overview Of the Electrophysiology Of The Sanmentioning
confidence: 99%